Quantification of Some Pesticide Residues in Milk Powder in Iraq by Gas Chromatography/ Mass Spectrometry - Ali , Ali Abdulla; Hassan , Khulod Ibrahim (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Pesticides are widely used on a global scale to improve productivity, but the persistent chemical residues they leave behind contaminate the environment and pose health risks to people. As a result, the current investigation was carried out to QuEChERS procedure adapted to gas chromatography coupled with mass spectrometry (GC–MS), to monitor the amounts of several organochlorine pesticides (OC), organophosphorus pesticides (OP), and pyrethroid in milk brand powder samples that were collected from Sulaimani market. About ten milk brand samples were analyzed to detect and quantify BHC, Chlorpyrifos, α-Cypermethrin, 2,4-D, Diazinon, and Endosulfan sulphate. Analytes provided acceptable responses at validation levels of 0.05 to 1 mg/kg. The linearity correlation coefficient R² was ≥ 0.9441, and limits of detection (LOD) value ranged from 0.18-0.49, limit of quantification (LOQ) value ranged from 0.54-1.49. Recovery percentage was obtained for all spiked levels (72.57-119.3) with acceptable relative standard deviation (RSD). The compounds α-Cypermethrin and Endosulfan sulphate found in most of the milk brands after that 2,4-D was found in brands but no one of them exceeded the MRL in all milk brands.